2013
DOI: 10.1007/s13204-013-0284-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural, optical and thermal properties of CdS:Zn2+ nanoparticles

Abstract: Undoped and Zn (1-5, 10 %) -doped CdS nanoparticles were successfully synthesized by chemical method and polyvinylpyrrolidone was used as capping agent. The morphology and crystalline structure of the samples were studied by transmission electron microscopy and X-ray diffraction. The average particle size of the spherical nanoparticles determined by these techniques was of the order of 2.5-6 nm. The functional groups of the capping agent on CdS:Zn 2? surface were identified by FT-IR study. The band gap of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Soltani et al [27] prepared ZnS by a microwave-hydrothermal method and obtained band gap energies 4.08-4.22 eV depending on microwave irradiation time. Muruganandam et al [28] reported that PVP-capped CdS via wet chemical method had a 2.6 eV band gap energy and 478 nm absorption edge, which then blue-shifted to 447 nm after doping with Zn 2+ . The FTIR spectra of the PVP-capped nanostructures were almost identical to that of pure PVP, as shown in figure 4.…”
Section: Characterization Resultsmentioning
confidence: 99%
“…Soltani et al [27] prepared ZnS by a microwave-hydrothermal method and obtained band gap energies 4.08-4.22 eV depending on microwave irradiation time. Muruganandam et al [28] reported that PVP-capped CdS via wet chemical method had a 2.6 eV band gap energy and 478 nm absorption edge, which then blue-shifted to 447 nm after doping with Zn 2+ . The FTIR spectra of the PVP-capped nanostructures were almost identical to that of pure PVP, as shown in figure 4.…”
Section: Characterization Resultsmentioning
confidence: 99%
“…It is expected that the Zn doped CdS will increase the efficiency of the solar cell. The effective mass approximation method is used to calculate the particles size with the following relation where E gn and E gb are the band gap values of nanocrystalline CdS and bulk CdS semiconductor (E gb = 2.4 eV), m* is the effective mass of the electron (= 0.19 m o , m o is the rest mass of electron) and R is the particle radius [34,35]. The particle size of the prepared samples was calculated and summarized in Table 3.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…They were able to synthesize nanoparticles below 10 nm. Muruganandam et al [22] synthesized CdS:Zn 2 + with PVP as capping agent. With the help of PVP, highly mono dispersed CdS nanoparticles were prepared which exhibited significantly enhanced luminescence and high chemical stability.…”
Section: Introductionmentioning
confidence: 99%